2019
DOI: 10.1186/s12898-019-0225-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of buffer strip width and selective logging on streamside plant communities

Abstract: BackgroundRiparian forests surrounding streams host high biodiversity values, but are threatened by clear-cut logging. Narrow buffer strips of about 15 m are commonly left between the stream and the clear-cut, but studies suggest that the buffer width should be at least 30 m to protect riparian plant communities. Moreover, selective logging is often allowed on the buffer strips in order to increase economic gain. We used an experiment of 43 riparian sites where buffer strip width and selective logging within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…Further, narrow buffers were associated with higher numbers of additional impairments connected to harvest operations (e.g., machine tracks, stream crossing, and drainage ditches). Although contemporary forest management practices that include buffers have substantially improved instream conditions in places where they have been implemented (Marczak et al, 2010; Oldén et al, 2019; Olson et al, 2007), buffers are still lacking for a large portion of the stream network. Bringing awareness to this problem is the first step to attain good ecological and biochemical status of all waters, and good conservation status for water‐related habitat types as required by, for example, the EU Water Framework Directive and EU Habitats Directive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, narrow buffers were associated with higher numbers of additional impairments connected to harvest operations (e.g., machine tracks, stream crossing, and drainage ditches). Although contemporary forest management practices that include buffers have substantially improved instream conditions in places where they have been implemented (Marczak et al, 2010; Oldén et al, 2019; Olson et al, 2007), buffers are still lacking for a large portion of the stream network. Bringing awareness to this problem is the first step to attain good ecological and biochemical status of all waters, and good conservation status for water‐related habitat types as required by, for example, the EU Water Framework Directive and EU Habitats Directive.…”
Section: Discussionmentioning
confidence: 99%
“…Partial harvesting within riparian buffers has been suggested as a potential strategy to balance economic and environmental goals in forestry (Sibley et al, 2012). Although upland harvesting will necessarily lead to some changes within the aquatic ecosystems, and no type of buffer can prevent them all; partially harvested buffers, if wide enough, seem to be an effective protection measure (Kreutzweiser et al, 2009(Kreutzweiser et al, , 2010Oldén et al, 2019). In addition, partial harvesting has been suggested to emulate natural disturbance (END) in the riparian corridor (e.g., forest fire) which may promote some ecosystem processes such as biodiversity, recruitment of broadleaf species in conifer-dominated stands, and more variable forest structure, which in turn may have positive feedback on aquatic ecosystems (Lidman et al, 2017;Mallik et al, 2014).…”
Section: 1029/2019wr026381mentioning
confidence: 99%
“…Number of species and individuals did not differ between buffers and control forests but were significantly lower in clearcut borders (Mönkkönen and Mutanen 2003). In another Finnish study, buffer strips of at least 30 m on both sides of streams were needed to maintain species composition of vascular plants but for mosses 15 m sufficed (Oldén et al 2019). For birds in Norway (Hågvar et al 2004), the number of species increased with buffer width, up to 30 m from the watercourse.…”
Section: Border Zones Along Watercoursesmentioning
confidence: 88%
“…It is notable that a 30 m buffer with the first 5 m unmanaged and 5-30 m managed with selective logging favoring broadleaves was slightly more cost-efficient than a 15 m unmanaged buffer for all three sites (Table 3). Oldén et al (2019b) studied the communities of vascular plants and mosses in an experiment in Finland and found that a 15 m wide buffer was not sufficient to protect the plant communities but they found no changes in 30 m wide buffers, whether selectively logged or not. On the other hand, when studying the microclimate in the same experiment Oldén Table 4.…”
Section: Managementmentioning
confidence: 99%